Innovative Methods of Teaching - Khamrakulov Utkirbek; Yusupov Arabboy Bahadirjon oglu; Mexmonalioev Shoxmuxammad; Xakimov Paxlavonjon (Zien Journals, 2021)
This article discusses modern teaching technologies and their role in the educational process.
Keywords: Interactive teaching; cognitive communication; cognitive activity; creative activity